بـــرنامـــج تنميــــــــــــة الأقــــــــــاليــم فـــــي العـــــراق بيـــــن منهـــــــج اللامركزية الإدارية وأهداف التنمية المحلية المستدامة للمدة 2006-2012 (المجلة العراقية للعلوم الاقتصادية, 2018)
Administrative decentralization in Iraq gained the status by the Constitution for the year 2005, which it was text on governorates not organized in a region the political and economic right. So legislation was supportive of this right by governorates not organized in a region law No (21) for the year 2008. This right was translated federal budget via investment allocations for the regions development program since 2006.Arise importance attention of sustainable local development in Iraq after it was exposure to decades from neglect and failures, causing the problem of inequality development levels among the governorates. This search came to provide a view of the official and local efforts to administrative centralization warning in local government system representative by governorates council, and its role in achieving the priorities of the Millennium Development Goals by rising of the financial implementation efficiency to investment allocations. It was specified in the regions development program in order to spatial development promote.